2017
DOI: 10.1016/j.juro.2016.09.083
|View full text |Cite
|
Sign up to set email alerts
|

Functional Effects of Bulbospongiosus Muscle Sparing on Ejaculatory Function and Post-Void Dribbling after Bulbar Urethroplasty

Abstract: Sparing the bulbospongiosus muscle during urethroplasty does not seem to have a significant impact on patient reported ejaculatory function or post-void dribbling compared with nonbulbospongiosus sparing urethroplasty at early followup.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 15 publications
0
4
2
1
Order By: Relevance
“…While the prevalence of PMI following urethroplasty has been described as up to 30% in prior evaluations 1 , this study found an even higher prevalence of this symptom than has previously been described. This result may be partially attributed to the fact that the questionnaire described in 2011 by Jackson et al…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…While the prevalence of PMI following urethroplasty has been described as up to 30% in prior evaluations 1 , this study found an even higher prevalence of this symptom than has previously been described. This result may be partially attributed to the fact that the questionnaire described in 2011 by Jackson et al…”
Section: Discussioncontrasting
confidence: 73%
“…Post-micturition incontinence (PMI), or post-void dribbling, is a lower urinary tract symptom that negatively affects quality of life in men, with a reported prevalence of nearly 30% 1 . PMI rates increase with age, thought to reflect slower transit of urine through the urethra secondary to prostatic growth, bladder dysfunction, and potentially, an age-dependent decrease in contractility of the bulbospongiosus muscle 2 .…”
Section: Introductionmentioning
confidence: 99%
“…13 This was further evaluated in a retrospective, multi-institutional, matched case-control study comparing muscle-sparing to non-muscle-sparing bulbar urethroplasty. 18 This study assessed pre-and post-operative ejaculatory dysfunction and, contrary to the initial report, found no benefit to muscle-sparing for preventing EjD.…”
Section: Discussioncontrasting
confidence: 65%
“…Later, Fredrick et al (49) designed a comparative study to evaluate the effects of BSM sparing during bulbar urethroplasty. Patients were assessed pre-and postoperatively with MSHQ as well as a patient perception questionnaire.…”
Section: Changes In Ejaculatory Function After Bulbar Urethroplastymentioning
confidence: 99%